Comparison of short-term efficacy of valproate sustained-release between adult and children as first-line monotherapy in management of partial epilepsy: A multicenter observational open-label study - Momin, Afzal; Habib, Ahsanul; Tarik, AKM Akramul Haque; Sikder, Mohiuddin A; Akter, Shaheen (Journal of National Institute of Neurosciences Bangladesh, 2015)
Background: Management of partial epilepsy is an important issue in the field of neurology. Objective: The purpose of the present study was to collect additional clinical data on efficacy and safety of sustained release sodium valproate chrono formulation as first-line monotherapy in patients newly or recently diagnosed with partial epilepsy in Bangladesh under daily practice condition. Methodology: This open-label, multicenter, non-controlled, prospective, observational study enrolled adults and children ? 6 years newly diagnosed with partial epilepsy with or without secondary generalization between March 2010 and February 2011. Patients were treated with sustained release sodium valproate. Primary evaluation criterion was the remission rate i.e. proportion of seizure-free patients at 6 months. Secondary evaluation criteria included retention rate at 6 months, remission rate at 1 and 3 months, investigator's global clinical impression rating, safety profile assessment. Results: A total of 185 adults and 115 children with mean 4.4 months duration of epilepsy were included. At inclusion the mean daily valproate dose in children was 329 mg and 568 mg in adults. The mean treatment duration in both children and adults was 5.5 months. At the end of 6 months 74.7% of the patients were seizure-free (children and adults; 79.1% vs 71.9%). The number of seizure free patients at 1 month was 109 (36.3%) and 175 (58.3%) at month 3. The treatment retention rate at 6 months was 87.3% with small higher trend in adults than children (88.6% vs. 85.2%). Among the patients 9.3% experienced side effects like drowsiness and weight gain. No severe adverse event was reported. Conclusion: Sodium valproate sustained release formulation is effective for the first-line treatment of partial epilepsy in both adults and children with acceptable tolerability J. Natl Inst. Neurosci Bangladesh 2015;1(1):2-4